Państwowość kazachska: historia i rzeczywistość. Przyczynek do teorii państwa - Osiński, Joachim; Baigunakov, Dosbol; Sabdenova, Gulmira (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The study attempts to present the most important facts related to the history of Kazakhstan. The paper also aims at introducing some theoretical remarks on the genesis and characteristics of states existing in different periods in Central Asia, particularly regarding Kazakh Khanate.